(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A significant challenge still remains for the development of drug delivery system (DDS) using herbal medicine for clinical applications. The present study describes a novel DDS consisting of a natural antibacterial drug berberine and silk fibroin (SF) for controlled drug delivery application. Composite films were synthesized using of SF and berberine mixtures at varied ratios. The unique structural features of SF molecules were analyzed using Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) during different film processing and post-processing conditions. Results revealed that water-annealed and glycerol modified method accurately controlled crystallization via modification of the secondary structure of the SF matrix and interaction with the non-crystalline domains, resulting in control of film degradation as well as drug diffusion rate. A linear relationship between crystallinity content (beta-sheet dominated silk II structure) and the release of entrapped berberine was achieved. The initial antibacterial activity of berberine retained for 4 days. The stability of the drug in SF film enhanced the intermolecular interactions between SF and berberine molecules. In conclusion, the composite materials consisting of SF and berberine have a great potential application as a DDS providing antimicrobial activities, such as antimicrobial suture and biomedical textiles.